Students attitudes towards reactivation of peer counselor program to prevent substance use - NURMALA, I.; RACHMAYANTI, R.D.; MUTHMAINNAH, MUTHMAINNAH; PERTIWI, E.P.; HARRIS, N.; PUSPITA DEVI, Y. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In this article, the attitud of high school students toward reactivation of the peer counsellor program in senior high schools is investigated. They were conducted in 10 high schools in 5 regions in Surabaya with a random sample of 854 students. The data were collected from July 2018 to September 2018 using a self-administered questionnaire. Results show that only 52.7% (n=450) of students knew about the program and 68% (n=581) of these students report a positive attitude toward the program. This research also found that a similar program exists in some schools. RESUMEN En este artículo, se investigan las actitudes de los estudiantes de secundaria hacia la reactivación del programa de consejeros de pares en las escuelas secundarias. Se llevaron a cabo en 10 escuelas y en 5 regiones de Surabaya con una muestra aleatoria de 854 estudiantes. Los datos se recopilaron de julio de 2018 a septiembre de 2018 mediante un cuestionario autoadministrado. Los resultados muestran que solo el 52.7% (n = 450) de los estudiantes conocían el programa y el 68% (n = 581) de estos estudiantes informaron una actitud positiva hacia el programa. Esta investigación también encontró que existe un programa similar en algunas escuelas.